Association of elevated glycated hemoglobin and obesity with afternoon napping for more than 1 h in young and middle-aged healthy adults - Al-Abri, Mohammed A.; Al Lawati, Ibtisam; Al Zadjali, Fahad (Frontiers in Psychiatry, 2022)
Introduction: Sleep present in different patterns worldwide and it can be influenced by social, cultural and environmental factors. Daytime napping is commonly practiced in different parts of the world with controversial results of its effect on glucose metabolism. The aim of the current study is to examine the association of afternoon napping and night sleep duration with metabolic derangements. Methods: This is a cross sectional study involved young adults and middle-aged subjects. Anthropometric measurements were taken for height and weight and hip and waist ratio. Consented subjects were asked to wear actigraphy for one week and run their usual daily activities. Home sleep apnea testing was performed to exclude obstructive sleep apnea. Subjects had been asked to come fasting on day seven for blood collection to test for fasting glucose, glycated hemoglobin, lipid profile and insulin. Results: Four hundred and five subjects completed the study (52% male, 48 % female). The mean age of participants was 32.8 ± 11.5 years. The study indicated that duration of afternoon napping was significantly associated with abnormal glycated hemoglobin (HbA1c >5.7%)(P=0.01) and body mass index (P=0.046) independent of age, gender and nocturnal sleep duration. nocturnal sleep duration was associated with increased insulin level (p=0.04). Conclusion: Afternoon napping is associated with increased level of glycated hemoglobin and obesity and that may predispose to the development of type 2 diabetes mellitus.